2015
DOI: 10.1002/pmic.201500049
|View full text |Cite
|
Sign up to set email alerts
|

Colonic metaproteomic signatures of active bacteria and the host in obesity

Abstract: Obesity is associated with the intestinal microbiota in humans but the underlying mechanisms are yet to be fully understood. Our previous phylogenetic study showed that the faecal microbiota profiles of nonobese versus obese and morbidly obese individuals differed. Here, we have extended this analysis with a characterization of the faecal metaproteome, in order to detect differences at a functional level. Proteins were extracted from crude faecal samples of 29 subjects, separated by 1D gel electrophoresis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 43 publications
0
42
0
2
Order By: Relevance
“…Members of the Bacteroidetes appear to be metabolically highly flexible. A recent proteomics analysis of obese and lean human gut microbiomes has highlighted that Bacteroidetes are more metabolically active in obese microbiomes despite their lower abundances [21]. Metabolic flexibility was demonstrated in a mouse model system by Sonnenburg and colleagues, who showed that when B. thetaiotaomicron was mono-associated with germfree mice, it exhibited a clear preference for certain substrates over others, and would alter gene expression to match changing substrate availability in its environment [22].…”
Section: The Phylum Bacteroidetesmentioning
confidence: 99%
“…Members of the Bacteroidetes appear to be metabolically highly flexible. A recent proteomics analysis of obese and lean human gut microbiomes has highlighted that Bacteroidetes are more metabolically active in obese microbiomes despite their lower abundances [21]. Metabolic flexibility was demonstrated in a mouse model system by Sonnenburg and colleagues, who showed that when B. thetaiotaomicron was mono-associated with germfree mice, it exhibited a clear preference for certain substrates over others, and would alter gene expression to match changing substrate availability in its environment [22].…”
Section: The Phylum Bacteroidetesmentioning
confidence: 99%
“…2012; Kolmeder et al . 2012, 2015). Metatranscriptomics analysis of fecal samples from 10 American adults revealed alterations in gene-expression profiles after changes in dietary intake (David et al .…”
Section: The Common Core Microbiome In the Human Large Intestinementioning
confidence: 99%
“…Similarly, metaproteomic comparison of 29 non-obese and obese adults has shown larger differences in the active functional bacteria between the two groups than those observed at the compositional level (Kolmeder et al . 2015). While these studies are a step toward functional understanding of the human microbiome, the field is still young.…”
Section: The Common Core Microbiome In the Human Large Intestinementioning
confidence: 99%
“…The study of Maurice et al [58] linked bacterial composition, activity, and expression to identify the active component of the gut microbiomta responding to xenobiotics. A recent metaproteomics study compared the level of bacterial proteins between obese and nonobese samples and identified the phylum Bacteroidetes was metabolically more active in the obese than nonobese samples [59]. These proof-of-concept studies demonstrate the power of a systems microbiology study in understanding function and dynamics of gut ecosystems and their role in the development of diseases.…”
Section: Toward Deeper Understanding In Lipid Metabolism and Functionmentioning
confidence: 95%